PERMAINAN â€œPOHON KATAâ€: SARANA PENINGKATAN KECERDASAN VERBAL LINGUISTIK ANAK USIA DINI - Anggraini, Nofita; Susilastri, Dian; Sudarmanto, Budi Agung (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstractâ€” Children are unique individuals with the development of extraordinary linguistic abilities. Children need guidance, support and positive stimulus from parents, educators, and the environment, including early childhood. The characteristics of each child are different, including with adults in terms of the learning process. The most enjoyable learning process for young children is playing, through playing children can learn and get new lessons, as well as learn to socialize with their peers. To communicate children need language, by speaking as a medium for delivery. One of the tasks of child development is to develop language skills, including honing their verbal linguistic intelligence. Development of children's verbal linguistic intelligence must be fostered from an early age. One means to help develop verbal linguistic intelligence is word play. The Word Tree Game is an educational tool in comprehensively honing, guiding, and directing the development of children's verbal linguistic intelligence. The Word Tree Game not only bridges children to hone linguistic verbal intelligence, but also (1) fosters the courage of children to speak, (2) practice their listening skills, (3) fosters mutual respect for peers, (4) creates physical attachment between children and educators or parents, (5) sharpening the ability to think and make decisions.Keywordsâ€”verbal linguistic, Words Tree, children gamesÂ Abstrakâ€” Anak adalah individu unik dengan perkembangan kemampuan linguistik yang luar biasa. Anak memerlukan bimbingan, dukungan dan stimulus yang positif dari orang tua, pendidik, dan lingkungannya termasuk anak usia dini. Karakteristik setiap anak berbeda-beda, termasuk dengan orang dewasa dalam hal proses belajar. Proses belajar yang paling menyenangkan bagi anak usia dini adalah bermain, melalui bermain anak dapat mengetahui dan memperoleh pelajaran baru, sekaligus belajar bersosialisasi dengan sebayanya. Untuk melakukan komunikasi anak memerlukan bahasa, dengan berbicara sebagai medium penyampaiannya. Salah satu tugas perkembangan anak adalah mengembangkan kemampuan berbahasa, termasuk mengasah kecerdasan verbal linguistiknya. Pengembangan kecerdasan verbal linguistik anak harus dibina sejak usia dini. Salah satu sarana untuk membantu mengembangkan kecerdasan verbal linguistik adalah adalah permainan kata. Permainan â€œPohon Kataâ€ merupakan sarana edukatif dalam mengasah, membimbing, dan mengarahkan perkembangan kecerdasan verbal linguistik anak secara komprehensif. Permainan â€œPohon Kataâ€ tidak hanya menjembatani anak untuk mengasah kecerdasan verbal lingusitik, tetapi juga (1) memupuk keberanian anak untuk berbicara, (2) melatih keterampilan menyimak anak, (3) menumbuhkan sikap saling menghargai sesama teman sebaya, (4) menciptakan keterdekatan fisik antar anak dan pendidik atau orang tua, (5) mengasah kemampuan berpikir dan membuat keputusan.Â  Â Kata kunciâ€” linguistik verbal, â€œPohon Kataâ€, permainan anak-anak